Epileptic Seizures Associated with Chromosomal Abnormalities Detected by Array Comparative Genomic Hybridization in Five Albanian Children - Babameto-Laku, Anila; Grabova, Serla; Vyshka, Gentian; Kruja, Jera (Journal of Pediatric Epilepsy, 2017)
Epilepsy is an ever-changing field of research, with genetics and genomics playing a very important role in recent times. Novel technologies detecting chromosomal aberrations are applied widely, and array-based comparative genomic hybridization (array CGH) has become a basic diagnostic tool in a variety of neurologic and neuropsychiatric conditions. The authors describe five Albanian children suffering from epilepsy and screened for genetic problems using array CGH and other methods. A thorough neurological examination and imaging studies were performed for all patients, who in addition to seizures, suffered from diverse medical conditions such as microcephaly, developmental delay, intellectual disability, dysmorphic features, heart anomalies, cryptorchidism, and other clinical stigmata of an aberrant neurodevelopment. It is evident from our case reports that the array CGH as a diagnostic tool in molecular genetics has facilitated the recognition of microdeletions and microduplications as risk factors for both generalized and focal epilepsies. This method, therefore, clearly has a practical and scientific value in the investigation of children with epilepsy and associated intellectual disability and congenital anomalies.
Keywords: epilepsy; seizures; chromosomal abnormalities; karyotype; array-based comparative genomic hybridization